Pengaruh Profesionalisme Dan Standrad Operating Procedure Terhadap Kinerja Karyawan Dengan Disiplin Kerja Sebagai Variabel Intervening Pada PT Usaha Sawit Mandiri (USM) Jorong Simpang Kecamatan Koto Balingka Kabupaten Pasaman Barat - Nika Yunita; Selvi Yona Sari; Bayu Pratama Azka (CV. ITTC INDONESIA, 2025)
This research aims to determine how much influence professionalism and standard operational procedures have on employee performance with work discipline as an intervening variable at PT. Mandiri Palm Oil Business Jorong Simpang, Koto Balingka District, West Pasaman Regency. The data collection method is through surveys and distributing questionnaires, using the SmartPLS application. The research results obtained were based on a partial test of the significant influence of professionalism on work discipline. There is no and insignificant influence of Standard Operating Procedures on Work Discipline. There is a significant influence between professionalism and employee performance. There is no significant influence of Standard Operating Procedures on Employee Performance. There is a significant influence of Work Discipline on Employee Performance. There is a significant influence of Professionalism on Employee Performance with Work Discipline as an Intervening Variable. There is no significant influence of Standard Operating Procedures on Employee Performance with Work Discipline as an Intervening Variable.